A unified approach to the estimation and interpretation of resistance costs in plants - Vila Aiub, Martin Miguel (2011)
Plants exhibit a number of adaptive defence traits that endow resistance to past and current abiotic and biotic stresses. It is generally accepted that these adaptations will incur a cost when plants are not challenged by the stress to which they have become adaptedthe so-called cost of adaptation. The need to minimise or account for allelic variation at other fitness-related loci (genetic background control) is frequently overlooked when assessing resistance costs associated with plant defence traits. We provide a synthesis of the various experimental protocols that accomplish this essential requirement. We also differentiate those methods that enable the identification of the trait-specific or mechanistic basis of costs (direct methods) from those that provide an estimate of the impact of costs by examining the evolutionary trajectories of resistance allele frequencies at the population level (indirect methods). The advantages and disadvantages for each proposed experimental design are discussed. We conclude that plant resistance systems provide an ideal model to address fundamental questions about the cost of adaptation to stress. We also propose some ways to expand the scope of future studies for further fundamental and applied insight into the significance of adaptation costs.